2016
DOI: 10.4103/0971-5916.187115
|View full text |Cite
|
Sign up to set email alerts
|

Isolation & characterization of Brucella melitensis isolated from patients suspected for human brucellosis in India

Abstract: Background & objectives:Brucellosis is endemic in the southern part of India. A combination of biochemical, serological and molecular methods is required for identification and biotyping of Brucella. The present study describes the isolation and biochemical, molecular characterization of Brucella melitensis from patients suspected for human brucellosis.Methods:The blood samples were collected from febrile patients suspected to have brucellosis. A total of 18 isolates were obtained from 102 blood samples subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Most misdiagnosed patients were admitted in Department of Rheumatology, Hematology, Orthopedics, and Respiration at the first visit. Brucella bacteria culture is the “gold standard” for the diagnosis of brucellosis [ 95 , 96 ]. In the study, 87% of brucellosis patients have fever.…”
Section: Discussionmentioning
confidence: 99%
“…Most misdiagnosed patients were admitted in Department of Rheumatology, Hematology, Orthopedics, and Respiration at the first visit. Brucella bacteria culture is the “gold standard” for the diagnosis of brucellosis [ 95 , 96 ]. In the study, 87% of brucellosis patients have fever.…”
Section: Discussionmentioning
confidence: 99%
“…Naturally, the Castañeda method is not specific for brucellae, and other microorganisms, including true pathogens and contaminants, may grow in the flask; therefore, full identification of the isolate is required. Although the performance of the Castañeda method has been superseded in recent years by automated blood culture systems, it is still extensively employed in countries of endemicity with limited economic and technical resources due to its low cost and practicality (27,(42)(43)(44)(45)(46)(47).…”
Section: Table 1 Factors That Determine the Positivity Rate Of Blood mentioning
confidence: 99%
“…melitensis [ 53 ]. Several studies have demonstrated that the 16S rRNA can be used as a rapid tool for Brucella identification [ 53 , 54 ]. In this study, we identified 38 Brucella isolates with PCR by targeting the 16S rRNA gene in the first round of screening and these were further identified as B .…”
Section: Discussionmentioning
confidence: 99%